DETERMINANTS OF LACMS ON KB ACCEPTORS IN THE WORK AREA OF DEPATI TUJUH HEALTH CENTER KERINCI REGENCY - Lia Nurdini; Puspita Sari; Rika Safitri (International Journal Of Health Science, 2022)
Family Planning Program (KB) using contraceptives is an effort to suppress the rate of population growth. In 2020, the proportion of LACMs (13.4%) in the working area of ​​the Depati Tujuh Health Center is smaller than the proportion of non-LACMs (86.6%) meaning that this achievement has not met the target of the 2020-2024 Strategic Plan (25.11%). The purpose of the research was to determine the determinants of the use of the Long-Acting Contraceptive Methods (LACMs) on family planning acceptors in the working area of ​​the Depati Tujuh Koto Tuo Health Center, Kerinci Regency. This type of research is quantitative research with a cross-sectional research design and an analytical survey research method. The number of research samples was 117 respondents who were taken using the proportional random sampling technique. Data collection in April-May 2021. The dependent variable is the use of LACMs while the independent variables are work status, knowledge, attitudes, husband's support, and the role of health workers. Data analysis using chi-square and cox regression. The results showed that the proportion of LACMs was 17.9%. There was a relationship between working status (PR=1.33; 95% CI=1.01-1.75), knowledge (PR=1.23; 95% CI=1.06-1.42), husband's support (PR= 1.30; 95% CI=1.10-1.53), and the role of health workers (PR=1.40; 95% CI=1.17-1.67) with the use of LACMs. There was no relationship between attitude (PR=1.15; 95% CI=0.98-1.36) with the use of LACMs. The dominant factor in the use of LACMs in the working area of ​​the Depati Tujuh Health Center in 2021 is the role of health workers (RR=6.34; 95% CI=1.45-27.71).